Early Years Management in Practice - Daly, Maureen; Byers, Elisabeth; Taylor, Wendy, 1958- (Harlow : Heinemann, 2009)
Fully up to date with the latest information and theories, this text supports students and practitioners working in early years management.
Previous ed.: 2004.
Includes bibliographical references and index.
Keywords: Early childhood education -- Management; Education